Code-dependent pathways for number transcoding: evidence from a case of selective impairment in written verbal numeral to arabic transcoding. - Macoir, J; Audet, T; Breton, M F (Cortex: A Journal Devoted to the Study of the Nervous System & Behavior, 1999)
This article presents a brain-damaged patient (RR) suffering from cognitive deficits following neurological insults, who showed a selective impairment in number transcoding. Except for written verbal numeral to arabic transcoding, his ability to transcode numerals, including writing arabic numerals to dictation, is largely preserved. Other number processing skills, including numeral recognition, numeral comprehension, and calculation, were unimpaired. Semantic and asemantic models of number processing cannot easily account for the patient's performance and it is suggested that the number transcoding system should include different code-dependent pathways for arabic transcoding from spoken verbal numerals and from written verbal numerals. Since the errors produced in the impaired transcoding rely upon the syntactical structure of numeral stimuli, it is also proposed that transcoding code-dependent pathways should reflect the structure of the verbal numeral system, especially the difference between sum and product relationships.